Implementation of Read-Answer-Disscuss-Explain-and Create Learning Model In Learning Explanation Text In Elementary School - Setiawan, Dadan; Sopandi, Wahyu; Handayani, Hany (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Increasing student mastery of learning material is one of the main goals in education. The purpose of this research is to describe the mastery of students' explanatory text concepts through the implementation of the Read, Answer, Disscuss, Explain, and Create (RADEC) learning models. The research method used in this study is a quasi-experimental method. The number of participants in this study were 38 students. Data were collected using a mastery test of explanatory text concepts. Data were analyzed through normality test, homogeneity test and t test using SPSS version 20.0 for windows. Based on the results of the study, it was found that the score of the students 'mastery of the concept of explanatory text concepts was 36.9 and the post-test scores of mastery of the concept of students' explanatory texts was 78.5. Based on the t test results it is known that p = 0.00 =0.05 means that there are significant differences in the mastery of students' explanatory text concepts between before and after treatment is given. Thus it can be concluded that the RADEC learning model is effective in developing the ability to master the explanatory text concept of elementary school students